Comandos de libertação nacional: oposição armada à ditadura em Minas Gerais - Isabel Cristina Leite da Silva (2009)
The following paper aims to analyze the performance of the group Comandos de Libertação Nacional (COLINA) in the universe of the Brazilian New Left. The group, which appeared as a disagreement of the theoretical organization called Política Operária (POLOP) in 1967, had great influence from the Cuban guerrilla and operated in the states of Minas Gerais and Guanabara. The theoretical issues which will feed the discussion refer to a definition of what terrorism would be, to political and communist cultures and to the assimilation of the idea of violence from COLINA, brought by a range of international authors. Lastly, a claim for the memory of the period by two militaries and two important inventories produced by them concerning the group ORVIL and AESI